2015
DOI: 10.3109/02713683.2015.1020169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visual Field Progression in Glaucoma: Quasar Regression Program and Event Analysis

Abstract: The combination of MD and PSD regression analysis in the Quasar program showed better agreement with the experts and higher sensitivity than GPA II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It seems clear that glaucoma is multifactorial and that individual susceptibility plays a role in the development and progression of the disease. Although high IOP is still the only known modifiable risk factor [13], the translaminar pressure gradient, i.e., the difference between IOP and cerebrospinal fluid pressure, has been identified as a risk factor for glaucomatous damage. This gradient is important in ocular diseases where the pressure on one or both sides of the lamina cribrosa is abnormally high or abnormally low [14].…”
Section: Discussionmentioning
confidence: 99%
“…It seems clear that glaucoma is multifactorial and that individual susceptibility plays a role in the development and progression of the disease. Although high IOP is still the only known modifiable risk factor [13], the translaminar pressure gradient, i.e., the difference between IOP and cerebrospinal fluid pressure, has been identified as a risk factor for glaucomatous damage. This gradient is important in ocular diseases where the pressure on one or both sides of the lamina cribrosa is abnormally high or abnormally low [14].…”
Section: Discussionmentioning
confidence: 99%
“…A linear function always has a straight-line graph, whereas an exponential function yields a curved graph. Previous studies on glaucoma progression have suggested that glaucoma damage progresses linearly, but the evidence supporting this is limited 10 12 .…”
Section: Introductionmentioning
confidence: 99%